Structure characterization of electrodeposited zinc selenide thin films - Mohamad, Souad A.; Basirun, Wan Jefrey; Ibrahim, Zainol Abidin; Mohd Arof, Abdul Kariem; Ebadi, Mehdi (Trans Tech Publications, Switzerland, 2011)

(untitled)
Crystalline thin of zinc selenide have been electrochemically deposited on conducting substrates of indium tin oxide, ITO glass. Initial investigation with voltammetry was done and shows that the zinc selenide films were stable towards oxidation. The best deposition potential obtained was at -0.95 V vs. Ag /AgCl while at lower deposition potentials, the films do not form well. Energy Dispersive Analysis and X-Ray spectrum indicate that the films deposited at 65oC and -0.95 V vs. Ag/AgCl have nearly stoichiometric Zn: Se ratio.